Transformations of random variables - Bikelis, Algimantas; Turkuvienė, Jurgita (Lietuvos matematikos rinkinys, 2005)
Transformation of random variable ξG ∼ GZD(α, β1,β2, δ, μ) is obtained in this article.
Keywords: generalized z-distribution; Levy characteristics; Gausian law; random variable transformation